Influence of Audio Visual Media Based on Project Based Learning (PjBL) on Students' Mathematical Reasoning Ability at College ERIA Medan High School - Oktami, Nurul Fauwzi; Octariani, Dhia; Rambe, Isnaini Halimah (Program Studi Pendidikan Matematika, Fakultas Ilmu Pendidikan, Universitas Timor, 2025)
This study discusses the influence of audio-visual media based on Project Based Learning (PjBL) learning towards the students’ mathematical reasoning at SMA Perguruan ERIA Medan. The sample technique was Purposive Sample with the type of Pre-Experimental Design (non-desaign) research. In this research design, only one class is used, namely the experimental class. In the learning process, treatment is given using audio-visual learning media based on Project Based Learning (PjBL).Data analysis used desciptive tests, normality tests, homogeneity test, and hypothesis test. Hypothesis testing used a simple linier regression test. The results of the study showed that the equation Y = 19,892 – 0,310X, with = 10.359 and significance value = 0.000 obtained the value of which is 10.359>2,0484 with a significance level of less than ∝ = 0,05. From the calculation results obtained the value of indicating that audio-visual media based on Project Based Learning (PjBL) towards the students’ mathematical reasoning of SMA Perguruan Eria Medan has a positive effect with a percentage of 79,3% including the high category. While acquisition of the students’responses was 82,3%. So, it can be stated that learning using audio-visual media based on Project Based Learning (PjBL) gets a positive response.